Repurposing matrine for the treatment of hepatosteatosis and associated disorders in glucose homeostasis in mice. (November 2018) - Mahzari, Ali; Zeng, Xiao-Yi; Zhou, Xiu; Li, Songpei; Xu, Jun; Tan, Wen; Vlahos, Ross; Robinson, Stephen; YE, Ji-Ming
Abstract The present study investigated the efficacy of the hepatoprotective drug matrine (Mtr) for its new application for hepatosteatosis and associated disorders in glucose homeostasis. The study was performed in two nutritional models of hepatosteatosis in mice with various abnormal glucose homeostasis: (1) high-fructose diet (HFru) induced hepatosteatosis and glucose intolerance from hepatic, and (2) hepatosteatosis and hyperglycemia induced by high-fat (HF) diet in combination with low doses of streptozotocin (STZ). Administration of Mtr (100 mg/kg every day in diet for 4 weeks) abolished HFru-induced hepatosteatosis and glucose intolerance. These effects were associated with the inhibition of HFru-stimulated de novo lipogenesis (DNL) without altering hepatic fatty acid oxidation. Further investigation revealed that HFru-induced endoplasmic reticulum (ER) stress was inhibited, whereas heat-shock protein 72 (an inducible chaperon protein) was increased by Mtr. In a type 2 diabetic model induced by HF-STZ, Mtr reduced hepatosteatosis and improved attenuated hyperglycemia. The hepatoprotective drug Mtr may be repurposed for the treatment of hepatosteatosis and associated disorders in glucose homeostasis. The inhibition of ER stress associated DNL and fatty acid influx appears to play an important role in these metabolic effects.